The Internet of Toys Practices, Affordances and the Political Economy of Children's Smart Play - Mascheroni, Giovanna; Holloway, Donell; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The Internet of Toys (IoToys) is a developing market within our Internet of Things (IoT) ecosystem. This book examines the rise of internet-connected toys and aims to anticipate the opportunities and risks of IoToys before their widespread diffusion. Contributors to this volume each provide a critical analysis of the design, production, regulation, representation and consumption of internet-connected toys. In order to address the theoretical, methodological and policy questions that arise from the study of these new playthings, and contextualise the diverse opportunities and challenges that IoToys pose to educators, families and children themselves, the chapters engage with notions of mediatization, datafication, robotification, connected and post-digital play. This timely engagement with a key transformation in children's play will appeal to all readers interested in understanding the social uses and consequences of IoToys, and primarily to researchers and students in children and media, early childhood studies, media and communications, sociology, education, social psychology, law and design. .
1. Introducing the Internet of Toys -- Part I - New toys, new play, new childhood? -- 2. Asking Today the Crucial Questions of Tomorrow: Social Robots and the Internet -- 3. The Uncanny Valley Revisited: Play with the Internet of Toys -- 4. Toying with the Singularity: AI, automata and imagination in play with robots and virtual pets -- 5. Postdigitality in children's crossmedia play: A case study of Nintendo's Amiibo figurines -- Part II - Domesticating the Internet of Toys: Practices and Contexts -- 6. The Domestication of Smart Toys: Perceptions and practices of young children and their parents -- 7. An Ecological Exploration of the Internet of Toys in Early Childhood Everyday Life -- 8. Persuasive Toy Friends and Preschoolers: Playtesting IoToys -- Part III - Design and Research methodologies -- 9. Designing the Internet of Toys for and with Children: A Participatory Design Case Study -- 10. Including Children in the Design of the Internet of Toys -- 11. Testing Internet of Toys designs to improve privacy and security -- 12. Video Methods: Researching Sociomaterial Points-of-View in Children's Play Practices with IoToys -- 13. Hybrid methods for hybrid play: a research toolkit -- Part IV - The Political Economy of IoToys -- 14. The Internet of Toys: Playing Games with Children's Data? -- 15. Covert advertising on IoToys -- 16. The industry of smart toys: cultural implications from the political economy -- 17. Concluding the Internet of Toys.
Keywords: Sociology; Social groups; Digital media; Educational technology; Sociology of Family, Youth and Aging; Digital and New Media; Digital Education and Educational Technology